Energy saving technology diffusion via FDI and trade: a CGE model of China - Michael Hübler (Kiel Institute for the World Economy (IfW), 2009)
This paper introduces intra- and inter-sectoral technology diffusion via FDI and imports into a recursive-dynamic CGE model for climate policy analyses. It analyzes China's accession to a Post Kyoto emission regime that keeps global emissions from 2012 on constant. Due to ongoing energy efficiency gains, partly stemming from international technology diffusion, China will become a net seller of emission permits and steadily reduce emissions, possibly below their 2004 level until 2030. This will reduce the world CO2 price significantly. The impact of supporting foreign firms and of reducing import tariffs on Chinese welfare will not significantly change when China joins the Post Kyoto regime.
Keywords: F18; F21; N75; O33; 330; Technology diffusion; technology transfer; trade; FDI; climate change; China; Direktinvestition; Technologietransfer; Energiesparen; Klimaschutz; Wirtschaftspolitische Wirkungsanalyse; Allgemeines Gleichgewicht; China